„Vasfüggöny a magyar államhatár mentén - Sallai, János (Közép-Európai Közlemények, 2009)
It was 20 years ago, that the iron curtain was demolished and the citizens of the DDR were released. With this action we greatly assisted the union of the DDR and GDR, and the dissolution of the socialist community. The iron curtain was built at the beginning of the cold war after the Second World War. In 1960 the former mine field was changed to this electric alarm system, which was invented by the soviets. In 1988 the Hungarian world passport was established, which permitted the Hungarian citizens of free travel. It greatly reduced the significance of the iron curtain. Finally 1989 the iron curtain was demolished, which made it possible to bypass the wall of Berlin and later it lead to the release of the DDR citizens. The study presents the whole story from the mine fields through the demolition of the iron curtain and finally the release of DDR citizens.